PET Molecular Imaging in Drug Development: The Imaging and Chemistry Perspective - Nerella, Sridhar Goud; Singh, Priti; Sanam, Tulja; Digwal, Chander Singh (Frontiers in Medicine, 2022)
The positron emission tomography (PET) with selective radioligands advances the drug discovery and development process at the earlier and late stages by revealing information about target engagement, proof of mechanism, pharmacokinetic and pharmacodynamic profiles. PET is an essential and highly significant tool to study therapeutic drug development, doses regimen, and drug plasma concentrations of a new drug candidates. On the other hand, the selective radioligands bring up target-specific information in several disease states including cancer, cardiovascular, and neurological conditions by quantifying various rates of biological processes with PET, which are associated with its physiological changes either in humans or animals, thus it reveals the disease progression and also advances the clinical investigation. Herein, it covers the major roles, applications, and advances of PET molecular imaging in drug discovery and development process with a wide range of radiochemistry as well as clinical outcomes of positron emitting carbon-11 and fluorine‐18 radiotracers.